A few north Appalachian populations are the source of European black locust. Issue 5 (16th February 2019) - Bouteiller, Xavier Paul; Verdu, Cindy Frédérique; Aikio, Emmi; Bloese, Paul; Dainou, Kasso; Delcamp, Adline; De Thier, Olivier; Guichoux, Erwan; Mengal, Coralie; Monty, Arnaud; Pucheu, Marion; van Loo, Marcela; et al.
Abstract: The role of evolution in biological invasion studies is often overlooked. In order to evaluate the evolutionary mechanisms behind invasiveness, it is crucial to identify the source populations of the introduction. Studies in population genetics were carried out on Robinia pseudoacacia L., a North American tree which is now one of the worst invasive tree species in Europe. We realized large‐scale sampling in both the invasive and native ranges: 63 populations were sampled and 818 individuals were genotyped using 113 SNPs. We identified clonal genotypes in each population and analyzed between and within range population structure, and then, we compared genetic diversity between ranges, enlarging the number of SNPs to mitigate the ascertainment bias. First, we demonstrated that European black locust was introduced from just a limited number of populations located in the Appalachian Mountains, which is in agreement with the historical documents briefly reviewed in this study. Within America, population structure reflected the effects of long‐term processes, whereas in Europe it was largely impacted by human activities. Second, we showed that there is a genetic bottleneck between the ranges with a decrease in allelic richness and total number of alleles in Europe. Lastly, we found more clonality within European populations. Black locust became invasive in Europe despite being introduced from a reduced part of its native distribution. Our results suggest that human activity, such as breeding programs in Europe and the seed trade throughout the introduced range, had a major role in promoting invasion; therefore, the introduction of the missing American genetic cluster to Europe should be avoided. Abstract : Black locust is an invasive tree species in Europe. In the present work, we showed that European populations are genetically close to few north Appalachian populations. Our results also suggest a limited bottleneck and a higher clonal propagation in the invaded range.